2021
DOI: 10.7759/cureus.17787
|View full text |Cite
|
Sign up to set email alerts
|

Study of Post-COVID-19 Syndrome in Saudi Arabia

Abstract: BackgroundPost-COVID-19 syndrome may be predisposed by organ damage as a complication of COVID-19. Patients may experience persistent symptoms after recovering from their initial illness. ObjectivesTo identify manifestations and predisposing factors for post-COVID-19 syndrome in Saudi Arabia. MethodsA cross-sectional study was conducted from May 2021 through June 2021 using an online structured precoded closed-ended, pilot-tested questionnaire in Arabic. It included male and female inhabitants of Saudi Arabia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
2
14
3
2
Order By: Relevance
“…Our study found a significant difference between outpatient and inpatient persistent symptoms, which is in agreement with a study conducted in Saudi Arabia that showed significant differences depending on the place of treatment [ 29 ]. Halpin et al concluded that patients admitted to ICU had a higher percentage of symptoms [ 12 ], whereas Garout et al found no relation between the severity of the disease and persistent symptoms [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study found a significant difference between outpatient and inpatient persistent symptoms, which is in agreement with a study conducted in Saudi Arabia that showed significant differences depending on the place of treatment [ 29 ]. Halpin et al concluded that patients admitted to ICU had a higher percentage of symptoms [ 12 ], whereas Garout et al found no relation between the severity of the disease and persistent symptoms [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Unlike the results of our study, headache as a neuropsychiatric symptom is a common persistent symptom after recovery from the acute phase of COVID-19 (44.0%) (23) , but it is more commonly found in patients who have been hospitalized (32,33) . The etiology of this type of residual symptom is complex and multifactorial and may be related to the direct effect of infection, cerebrovascular disease (including hypercoagulation) (34) , physiological impairment (hypoxia), side effects of medication and social aspects of having a potentially fatal disease (35) .…”
Section: Discussioncontrasting
confidence: 99%
“…Although there is no consensus across reviews and original research articles on the definition of post-COVID-19 syndrome, guidelines from the National Institute for Health and Care Excellence (NICE) define it as a group of signs and symptoms that are present for >12 weeks, developed during or after infection with SARS-CoV-2, and cannot be attributed to alternative diagnoses 101 . Musculoskeletal symptoms in this syndrome include fatigue, arthralgia, myalgia, new-onset back pain, muscle weakness, and poor physical performance 10,14,16,25,33,35,36,39,40,43-45,49,55-57,61,64 . Since COVID-19 is a relatively new disease, the literature lacks follow-up data to determine the natural history of post-COVID-19 syndrome and its management.…”
Section: Discussionmentioning
confidence: 99%